Engineering of Metabolic Pathways Using Synthetic Enzyme Complexes. Issue 3 (19th November 2018) - Smirnoff, Nicholas
Abstract : Prospects are reviewed for the use of synthetic enzyme complexes as a metabolic engineering tool.